2019
DOI: 10.1177/0011128719881600
|View full text |Cite
|
Sign up to set email alerts
|

Time, Money, and Punishment: Institutional Racial-Ethnic Inequalities in Pretrial Detention and Case Outcomes

Abstract: While prior research finds that pretrial detention has downstream consequences for racial inequalities in conviction and sentencing, it is often conceptualized as a discrete event within the criminal justice system. This study instead argues that pretrial detention operates as a racial-ethnic stratification process across time. We assess whether temporal and monetary dimensions of pretrial produce and reinforce racial-ethnic disparities in pretrial and subsequent case outcomes. Results indicate that time and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 70 publications
3
31
0
Order By: Relevance
“…In line with cumulative disadvantage studies finding that earlier decisions have downstream consequences (Kutateladze et al., 2014; Schlesinger, 2007), we find that pretrial detention explains inequality in conviction and jail sentences. Since Black people in Miami‐Dade's criminal justice system are disproportionately pretrial detained, they are disadvantaged in the plea‐bargaining process (Martinez et al., 2019). Although some research has examined the influence of pretrial detention (Schlesinger, 2007), charging (Owens et al., 2017), and plea‐bargaining (Bushway & Piehl, 2007) on disparate case outcomes, more work is needed given that sentencing inequalities reflect the culmination of a series of prior decisions (Fischman & Scanzenbach, 2012; Rehavi & Starr, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In line with cumulative disadvantage studies finding that earlier decisions have downstream consequences (Kutateladze et al., 2014; Schlesinger, 2007), we find that pretrial detention explains inequality in conviction and jail sentences. Since Black people in Miami‐Dade's criminal justice system are disproportionately pretrial detained, they are disadvantaged in the plea‐bargaining process (Martinez et al., 2019). Although some research has examined the influence of pretrial detention (Schlesinger, 2007), charging (Owens et al., 2017), and plea‐bargaining (Bushway & Piehl, 2007) on disparate case outcomes, more work is needed given that sentencing inequalities reflect the culmination of a series of prior decisions (Fischman & Scanzenbach, 2012; Rehavi & Starr, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have also found that pretrial detention creates inequalities in conviction and sentencing (Jones, 2013; Martinez, Petersen, & Omori, 2019; Schlesinger, 2007; Stevenson, 2016). This pattern is highlighted by the cumulative disadvantage perspective, which suggests that initial disadvantages in early stages produce compounding sentencing disparities (Kutateladze et al., 2014; Omori, 2019; Spohn, 2000; Sutton, 2013; Zatz, 1987, 2000).…”
Section: Institutionalized Inequality In Criminal Courtsmentioning
confidence: 99%
See 3 more Smart Citations